AN EVALUATION ON TEFL 1 SYLLABUS OF ENGLISH DEPARTMENT: A RATIONAL- BASED MODEL - Ilham, Ilham (JURNAL SMART, 2019)
Curriculum is the design to carry out a particular language program, including subject-matter objectives, sequencing and materials to meet the needs of a designated group of learners in a defined context (Brown, 2000).  The objective of this study is to depict the academic English language curriculum/syllabus of TEFL 1 subject in English Department UM Mataram. The present study analyzes the coherence, consistency, and relevance of the curriculum objectives, content, learning activities, and assessment, institution vision and mission, law, and the nature of the subject matter. Tyler’s rationale model is utilized in analyzing the documents. The result of this study can be used as some considerations in reconstructing the syllabus so that learning experiences will be relevant and consistent with the learning objectives stated in the syllabus.